„Nosce te ipsum” — Introduction to the Study - Urbańska, Monika; Agnieszka Gralak (Lustro, 2020)
The introduction to the MIRROR study shows the etymology of the term in different languages (Polish, French, Latin, Greek) and its meaning in different cultures. The mirror is a symbol that can be read on many levels. In interdisciplinary discourse, the mirror functions not only as an object — it is also a symbol of internal reckoning and self-knowledge. In Lacan’s theory, a mirror is a kind of landmark for a child, designating them as a being separate from the environment and controlling their previously disintegrated body. Mirrors on a massive scale were manufactured at the beginning of the 15th century, but they belonged to luxury goods reserved for decorating palaces. Mirror often appeared in folk beliefs, literature and art. In Greek mythology, it was an attribute of Aphrodite — the goddess of beauty, it also became the cause of the misfortune of Narcissus. This subject also inspired painters. In seventeenth-century Europe, the penchant for mirrors was established in interior architecture, painting, philosophy and literature. Contemporary architecture uses a mirror as an important element in creating light and space, as well as a decorative detail that adds modernity. Today, the mirror is still fascinating, installations are exposing the mirror surfaces all over the world. The volume on the MIRROR motif includes articles by seven researchers in literature, language and culture, showing the issue of self-recognition in contact with a mirror prop throughout the ages. As a symbol, the mirror appears, among others, in the context of translation, language, communication codes and persuasion. Interestingly, also elements of nature designed by people of different eras can be read as mirrors reflecting the features of their owners and times.